2013
DOI: 10.1037/a0030561
|View full text |Cite
|
Sign up to set email alerts
|

Striving to feel good: Ideal affect, actual affect, and their correspondence across adulthood.

Abstract: The experience of positive affect is essential for healthy functioning and quality of life. Although there is a great deal of research on ways in which people regulate negative states, little is known about the regulation of positive states. In the present study we examined age differences in the types of positive states people strive to experience and the correspondence between their desired and actual experiences. Adults aged 18–93 years of age described their ideal positive affect states. Then, using experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
120
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(150 citation statements)
references
References 70 publications
22
120
2
Order By: Relevance
“…Thus, although happiness may decrease in old age, other positive emotions may remain stable or increase. For example, a recent study conducted by Scheibe, English, Tsai, and Carstensen (2012) suggests that whereas positive emotions characterized by high arousal (i.e., excited, proud) decline with age, positive emotions characterized by the absence of arousal (i.e., calm, relaxed) remain stable (for similar evidence see Kessler & Staudinger, 2009). …”
Section: The Quality Of Affective Experience During Old Agementioning
confidence: 97%
“…Thus, although happiness may decrease in old age, other positive emotions may remain stable or increase. For example, a recent study conducted by Scheibe, English, Tsai, and Carstensen (2012) suggests that whereas positive emotions characterized by high arousal (i.e., excited, proud) decline with age, positive emotions characterized by the absence of arousal (i.e., calm, relaxed) remain stable (for similar evidence see Kessler & Staudinger, 2009). …”
Section: The Quality Of Affective Experience During Old Agementioning
confidence: 97%
“…Since this original report, various studies have also found links between actual and ideal affect discrepancies and other indices of health (i.e., physical symptoms [43], as well as depression and life satisfaction [4445]) across a variety of cultures. However, it is less clear whether there are cultural differences in the types of discrepancies that matter for health.…”
Section: The Roles Of Ideal Affect In Healthmentioning
confidence: 99%
“…Indeed, age-related decreases in negative emotion are most apparent for high arousal states (e.g., anger, rage, despair; Lawton et al, 1992;Phillips et al, 2008;Ross and Mirowsky, 2008;Schieman, 1999). Additionally, Scheibe et al (2013) recently reported an age-related increase in daily low arousal positive emotions in a sample spanning young adulthood to old age, while high arousal positive emotions were age invariant. They also asked participants about preferences for specific emotions and found that older people preferred low arousal positive states (e.g., calm) over high arousal positive states.…”
Section: Age Differences In Emotional Experiencementioning
confidence: 99%